2015
DOI: 10.4236/eng.2015.73011
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation Solutions in Renovated Apartment Buildings in Cold Climate Conditions

Abstract: Different solutions of renovating the ventilation in apartment buildings have been researched.The analysis shows that the use of heat recovery in cold climate regions is essential. Central as well as apartment-and room-based solutions with heat recovery have been studied. Balanced ventilation is suitable for small (2 -3-storey) apartment buildings with a suitable room solution for apartments. In larger apartment buildings, the system with the exhaust air heat pump could be used. This is particularly suitable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…They also found that the total electricity consumption of fans was twice as high in centralized ventilation units as compared to apartment-based units, indicating that a decentralized ventilation system also has energy-saving potential over a centralized ventilation system. Koiv et al (2015) [16] studied different ventilation strategies using a simulation approach. Their work included simulations of centralized systems, apartmentand room-based systems, and systems with heat recovery in low-rise apartment buildings in cold climates.…”
Section: Previous Studies On Ventilation Strategies In Mf Buildingsmentioning
confidence: 99%
“…They also found that the total electricity consumption of fans was twice as high in centralized ventilation units as compared to apartment-based units, indicating that a decentralized ventilation system also has energy-saving potential over a centralized ventilation system. Koiv et al (2015) [16] studied different ventilation strategies using a simulation approach. Their work included simulations of centralized systems, apartmentand room-based systems, and systems with heat recovery in low-rise apartment buildings in cold climates.…”
Section: Previous Studies On Ventilation Strategies In Mf Buildingsmentioning
confidence: 99%
“…To improve the energy efficiency in the existing buildings, retrofitting is required. The optimal solution for the building retrofit depends on the existing ventilation system and climate conditions [10]. In old buildings with low thermal insulation and poor airtightness, the energy efficiency of the building envelope, together with an improved ventilation heat recovery, should be considered to meet the current European requirements for energy efficiency [11].…”
Section: Introductionmentioning
confidence: 99%
“…In old buildings with low thermal insulation and poor airtightness, the energy efficiency of the building envelope, together with an improved ventilation heat recovery, should be considered to meet the current European requirements for energy efficiency [11]. The standard ways for a retrofit are to replace the original ventilation system with balanced mechanical ventilation or to implement a heat pump together with exhaust airflow energy recovery [10,12,13]. Mechanical exhaust systems equipped with heat pump heat recovery and ventilation radiators are common solutions e.g., in Sweden [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the AAHX is an easy solution to reduce energy requirements mainly in existing buildings, originally designed only with a natural ventilation system or with mechanical ventilation [3,4].…”
Section: Introductionmentioning
confidence: 99%